TINGKAT KEPUASAN KONSUMEN TERHADAP PRODUK BUAH LOKAL DI FRESHMART TIKALA KOTA MANADO - Natanael ., Siagian; Melissa Lady Gisela Tarore; Leonardus Ricky Rengkung (Sam Ratulangi University, 2021)
This study aims to determine the level of satisfaction of local fruit consumers with products, prices, locations, and promotions at Freshmart Tikala, Manado City. This research was conducted for 3 months starting from April to June 2021. The data used were primary and secondary data. Primary data was taken from filling out a questionnaire with 35 respondents and secondary data was taken from Freshmart Tikala with Likert scale measurements and secondary data from the literature that supports and has a relationship with this research. The data analysis method used is descriptive data analysis. The sampling method was carried out using a non-probability technique with an accidential sampling design. The results of this study are the level of consumer satisfaction from the product, price, place, and promotion variables gets very satisfied criteria because the percentage results are between 80% - 100% while the promotion and location variables get satisfied criteria because the percentage results are between 60%-80%.